Analysis of Work Ability, Work Discipline, and Non-Physical Work Environment on the Performance of ASN Employees at the North Sumatra Provincial Manpower Office - Intan Gusnita; Daud Arifin; Samrin Samrin (Journal of Management, Economic, and Accounting, 2026)
This study aimed to analyze the effect of work ability, work discipline, and non-physical work environment on the performance of civil servant employees at the Department of Manpower of North Sumatra Province. The study used a quantitative approach with an associative method. The research population consisted of 215 civil servant employees, with a sample of 69 respondents selected using the Slovin formula through purposive sampling. Primary data were obtained through the distribution of questionnaires, and the results were processed using SPSS software version 24. Data analysis was conducted using multiple linear regression to examine the relationship between the independent variables and the dependent variable. The results showed that work ability, work discipline, and non-physical work environment, both partially and simultaneously, had a positive and significant effect on employee performance. Work ability was the most dominant variable influencing employee performance, as indicated by the highest regression coefficient. The coefficient of determination (adjusted R²) was 0.920, indicating that 92.0% of the variation in employee performance was explained by the three independent variables, while the remaining 8.0% was explained by other variables not included in this research model. In addition, the strength of the relationship between the independent variables and the dependent variable was categorized as very strong, with a correlation coefficient (R) of 0.961.